How to Train Language Teacher Trainers. - Diadori, Pierangela (Cambridge Scholars Pub., 2012)
In recent decades, considerable European investment has been devoted to the training of language assistants, full-time teaching staff and mentors, while the new figure of the professional "language teacher trainer" (LTT) has emerged. It is becoming increasingly important that future LTTs are not simply more expert teachers, or scholars competent in the various relevant disciplines, but professionals who are aware of their role, who know the development of teacher training in Europe and beyond ...